A Trans‐Acting Ketoreductase in Biosynthesis of a Symmetric Polyketide Dimer SIA7248. Issue 6 (15th March 2013) - Zou, Yi; Yin, Haixing; Kong, Dekun; Deng, Zixin; Lin, Shuangjun
<x xml:space="preserve">Abstract</x> New assembly line, new compound: SIA7248, a new symmetric macrolide, was isolated from a marine‐derived Streptomyces strain. Bioinformatic analyses of the identified biosynthetic gene cluster (sia) for SIA7248 suggested a polyketide biosynthesis utilizing an iteratively trans‐acting ketoreductase (KR). We characterized SiaM as a trans‐KR to catalyse reductions of various β‐ketoacyl‐thioesters with D‐stereospecificity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>